Richard Rolle: on lamentations$da critical edition with translation and commentary - Rolle, Richard (Exeter Medieval Texts and Studies, 2020)
"This volume presents the first study, critical edition, and translation of one of the earliest works by Richard Rolle (c. 1300-1349), a hermit and mystic whose works were widely read in England and on the European continent into the early modern period. Rolle’s explication of the Old Testament Book of Lamentations gives us a glimpse of how the biblical commentary tradition informed what would become his signature mystical, doctrinal, and reformist preoccupations throughout his career. Rolle’s English and explicitly mystical writings have been widely accessible for decades. Recent attention has turned again to his Latin commentaries, many of which have never been critically edited or thoroughly studied. This attention promises to give us a fuller sense of Rolle’s intellectual, devotional, and reformist development, and of the interplay between his Latin and English writings."